Deni PENGGUNAAN MEDIA VIDEO AKUN INSTAGRAM INFOJAWABARAT DALAM MENINGKATKAN DAYA KREATIVITAS SISWA KELAS X SMA - Deni; Fahruroji, Fahruroji; Apriliyani, N Yeffa Afnita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Students still need help writing poetry because they cannot determine a theme or image to use as inspiration. This study aimed to determine whether class X students of SMA Negeri 25 Bandung in the 2022/2023 academic year can write poetry more creatively, thanks to video content from the Instagram infojawabarat account. The true experimental design method was used in this study. The pretest-posttest control group design was used in this study. Based on the calculation results of the Normality Test, abnormal Significance data is generated. Then test the hypothesis using the Wilcoxon test; it is known that the output test Statistics is known as Asymp. Sig. (2-tailed) is 0.001. Because the value of 0.001 <0.05,